Effectiveness of Sterilization by Microwave Irradiation on Polyvinyl Siloxane Contaminated with Candida Albicans: An Invitro Study - Noor S. Almoula; Aliaa W. Al-Omari (University of Mosul, College of Dentistry, 2024)
Aims: This in-vitro study aimed to evaluate the effect of microwave irradiation on polyvinyl siloxane impression material contaminated with candida Albicans. Materials and methods: 30 samples were fabricated from the acrylic mold with disk shape 5*2 (diameter*thickness). Samples incubated with Brain Heart Infusion Broth (BHI) media containing Candida albicans. Then were divided into 30 samples into 6 groups: C (positive control); 5 non-irradiated specimens, 3MWD ( samples irradiated for 3minute in dry condition), 6MWD (samples irradiated for 6minute in dry condition), 3MWW (samples irradiated for 3minute in wet condition), 6MWW (samples irradiated for 6minute in wet condition), CHX (samples immersed in 0.5% chlorhexidine) After incubation of all samples for 24 hours at 37°C, the samples were got vortex and then serial dilution carried out of suspensions then cultured on Sabouraude Dextrose Agar after incubation for 24 hours at 37°C bacteria were counted. A further 7 days of incubation for microwaved samples was done to verify the effectiveness of both dry and wet microwave sterilization for two periods of time. Results: There was a significant reduction in cfu /ml of candida albicans at 24 hours of incubation. No growth of C. albicans was recorded after 7 days of incubation. Conclusions: Microwave irradiation at 640W for both wet and dry conditions for 3 and 6 min was proved to be effective in the disinfection of polyvinyl siloxane specimens contaminated with. Candida. albicans.